The Effect of Job Stress on Employee Performance at Holiday Inn Resort Baruna Bali - Devi, Ni Made Githa Hapsari Kaniya; Sihombing, Irene Hanna H; Adinda, Clearesta (CV. Publikasi Indonesia, 2024)
Job stress is an important factor that can affect employee performance in a company, especially in the hospitality industry which faces high pressure and consistent service demands. This study aims to examine the effect of job stress on employee performance at Holiday Inn Resort Baruna Bali. This research uses a quantitative approach with a sample size of 110 respondents with a total sampling method, namely saturated samples. Data collection was carried out by distributing digital questionnaires through Google Forms, which used a 5-point Likert scale. Data analysis techniques used are classical assumption test, simple linear regression, t-test and coefficient of determination. The results of this study indicate that job stress has a negative and significant effect on employee performance. The job stress variable is negative with a beta value of -0.496 An increase in job stress (X) will result in a decrease in employee performance.